A determination of the standards of morphometrics variables of the stomatognathic system of a fetus - Salaga-Nefic, Samra; Mehmedbasic, Senad; Kozadra, Jasmina; Zukanovic, Amila; Tiro, Alisa; Dzemidzic, Vildana; Nakas, Enita (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2019)
Introduction: Many factors affect the growth and development of the mandible. The most common one is micrognathia; this can poseand neonatal emergency. Early recognition of mandibular and other face anomalies could provide immediate care for these infants,and presence of neonatologist or other doctors in the delivery room.The aim: Aim of this study was to develop normal ranges of the facial markers: mandibular length, jaw index and the facial angle inthe fetus using 3D ultrasound.Material and methods: The research was conducted as a cross-sectional study in the second trimester of pregnancy. Fetuses (femalen=23 and male n=27) from singleton pregnancy between 29-37 week of gestation were examined by ultrasound. All images wereacquired transabdominally, using Voluson E16. Ultrasound was performed by an experienced operator (SM) and measured thevalues of head circumference, abdominal circumference, biparietal diameter, femur length, body mass. For mandibular length,inferior facial angle, and the jaw index was calculated (Jaw Index =AP mandibular diameter / BPD * 100), the profile images wereused (only images in the exact midsagittal plane were used). The characteristics of the fetal profiles were determined by the Schwartzand Ricketts profile analysis using soft tissue landmarks and analysis of the profile photographs.Results: The results show that the jaw index ranged from 25.33 and 34.06 with an average of 26.00 for all examined fetuses.Conclusion: The physiological position of the mandible is retrognathic and that the average physiological length of the mandible inthe third trimester is 2.31cm. There is no difference in mandibular length between genders.